PENGEMBANGAN BAHAN AJAR MENULIS PUISI BERKONTEKS LINGKUNGAN PESERTA DIDIK BERMUATAN NILAI-NILAI RELIGIUS UNTUK MADRASAH ALIYAH - Arisul Ulumuddin (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
Instructional materials to write poetry in the Indonesian language andliterature curriculum perluh developed based on the needs of learners. In thedevelopment of teaching materials for Madrasah Aliyah poetry should be adaptedto the context of the learners who have religious values by integrating religiousvalues. This study aims to identify the needs of the students and teachers in thedevelopment of teaching materials poetry student environment contextual chargedreligious values for madrasah aliyah, decrypt the characteristics of poetryteaching materials developed contextual environment students charged religiousvalues for madrasah aliyah, and determine the effectiveness of the use of teachingmaterials poetry student environment contextual charged religious values formadrasah aliyah. Based on the analysis and discussion of the results of researchon teachers and learners need instructional materials Islamic senior-laden poetryreligious values derived from a true story. Based on the stage of development ofteaching materials obtained by writing poetry student environment contextualcharged religious values for madrasah aliyah entitled Easy Ways to Write Poetry.Book-laden religious values have been expressed and decent by experts andaccepted by the public, especially the students and teachers of Madrasah Aliyah.Teaching materials poetry contextual environments learners laden religiousvalues have aspects effectiveness after limited testing at MAN 1 Semarang.Keywords: development of teaching materials, writing poetry, the students,religious values